Pengaruh Pendidikan Kesehatan Perawatan Kaki Terhadap Tingkat Pengetahuan Dan Sikap Pada Penyandang Diabetus Di Persadia RSUP dr. Soeradji Tirtonegoro Klaten - Gistama, Didit; , Arina Maliya, S.Kep., M.Si.Med (2017)
Background: Diabetes mellitus is a chronic disease that each year the prevalence is increasing. One of the complications of diabetus mellitus ulcers diabetic is. Foot care is one of the primary prevention efforts aimed at preventing the occurrence of injuries. Sufferers lack knowledge in the care of the feet will be foot ulcer diabetic could happen and will grow soured otherwise get health education. Research objectives: find out the influence of health education against diabetic foot care knowledge and attitude level in patients of Diabetes Mellitus was Persadia group Dr. Soeradji Tirtonegoro Klaten. Research methods: This type of research is experimental research design quasy One Group PrePost Test With Control Design with cross sectional approach to the subject. Engineering samples are non probability sampling with technical purposive samplingof asmany as 80 respondents. Techniques of data analysis using the Mann Whitney test test. Results of research: Characteristics of the respondent based on the gender of the majority of women 71 (88.75%) based on the age most 41-60 years by as much as 47 (59.75%), based on the level of education of most of the High School as many as 24 (30%) and based on the kind of work most are employees of the private sector as much as 32 (40%). The level of knowledge prior to health education is quite 20 (25%) and after health education increased to as many as good 43 (53.75%). The attitude of the before the health education was 24 (30%) while on Post test with 35 (43.75%) or statistically respondents after health education Attitude increased 3.1 times better. Summary: Statistically with Mann Whitney test there is the influence of health education to knowledge of diabetic foot treatment with a value of p = 0000. There is the influence of health education against the attitude of diabetic foot treatment with a value of p = 0000. Keywords: health education, level of knowledge, attitudes